2020
DOI: 10.1155/2020/8864764
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on Response to Online Customer Reviews and E-Commerce Sales: From the Mobile Information System Perspective

Abstract: Response to online customer reviews helps increase sales. Extensive research has been carried out on this topic discussing tactics of response, while few scholars looked at it from the social network perspective. The problem is not how to respond but to whom to respond. Essentially, it is an effective online social network, not a response itself that generates trust and sales. In this paper, our main work is to use basic theoretical tools of social network theory to reveal the nature of the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 66 publications
0
17
0
2
Order By: Relevance
“…Hadiana A selected ten mobile information system samples about the education system as specimens suitable for designing the interface of the parenting information system [4]. Multivariate statistical analysis (such as factor analysis (FA) and partial least squares (PLS)) was used to process data questionnaires collected from thirty respondents [5,6]. rough the research, he found that when designing the user interface of a mobile parent information system, two important emotional factors must be considered, namely, interest and benefit [7,8].…”
Section: Related Contentmentioning
confidence: 99%
“…Hadiana A selected ten mobile information system samples about the education system as specimens suitable for designing the interface of the parenting information system [4]. Multivariate statistical analysis (such as factor analysis (FA) and partial least squares (PLS)) was used to process data questionnaires collected from thirty respondents [5,6]. rough the research, he found that when designing the user interface of a mobile parent information system, two important emotional factors must be considered, namely, interest and benefit [7,8].…”
Section: Related Contentmentioning
confidence: 99%
“…In order to be compatible with most external devices, the most advanced devices provide various forms of hardware interfaces, such as UART, USB, and wireless transmission interfaces [9]. When there are many sensors sending data to the most advanced equipment [10], whether it is physical data or network data, it must be cleared by the data processing unit inside the device [11,12]. After that, the data are uploaded to the cloud in a predefined format [13,14].…”
Section: The Methods Of Continuous Use Behavior Of Knowledge Payment Platform Based On Edge Computing Under Mobile Information Systemmentioning
confidence: 99%
“…must be designed and constructed with high reliability to improve the safety and reliability of the entire digital community computer network and application system (5) Scalability: the construction of the digital community needs to be gradually and continuously expanded. For this reason, the system needs to adopt component technology to support the combination, inheritance, and online definition of applications [25] 3.3. Module Function Design of the System.…”
Section: System Design Principlesmentioning
confidence: 99%